PREPAREDNESS RADIOLOGICAL SERVICES FOR THE COVID-19 EMERGENCY HOSPITAL IN WISMA ATLET KEMAYORAN - Muhammad Irsal (Politeknik Kesehatan Kemenkes Jakarta II, 2021)
Effort reducing the severity of COVID-19, a flattening of the curve is needed which aims to prepare the treatment system so that the capacity of the hospital can treat patients and provide health care workers, to meet the minimum standard of radiological services during the pandemic, therefore necessary planning and control of radiology services to patients. This research is quantitative descriptive by analyzing the data and discussing the literature, the research was conducted in March-June 2020 in the department radiology of the COVID-19 Emergency Hospital in Wisma Atlet Kemayoran. Subjects of the study were department radiology readiness: facilities radiology, equipment, and conditions of workers, analysis of radiological services, as well as radiation protection and safety for workers and patients. Results for radiology facilities and equipment are very adequate in carrying out radiographic examinations, workers equipped with PPE according to standard operating procedures for handling COVID-19, Radiology services based on workload indicator staff need (WISN) analysis required 16 radiographers with an estimated number of chest radiograph examinations of 4000 patients, and 1 medical physicist. In applying for radiation protection, we must pay attention to the principles of distance, time, and shielding.